2021
DOI: 10.1021/jacs.1c05112
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Electric Fields at the Water–C12E6 Surfactant Interface

Abstract: We study the properties of the interface of water and the surfactant hexaethylene glycol monododecyl ether (C12E6) with a combination of heterodyne-detected vibrational sum frequency generation (HD-VSFG), Kelvin-probe measurements, and molecular dynamics (MD) simulations. We observe that the addition of the hydrogen-bonding surfactant C12E6, close to the critical micelle concentration (CMC), induces a drastic enhancement in the hydrogen bond strength of the water molecules close to the interface, as well as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…Both SDS and C 12 E 6 are widely used surfactant systems and have been studied extensively before. The interfacial structure of aqueous solutions of C 12 E 6 has recently been studied using HDVSFG, Kelvin-probe measurements, and molecular dynamics (MD) simulations 29 . In this study, it was found that C 12 E 6 at CMC (70 µm) generates a strong electric eld of 1 V/nm arising from the orientational structure of both the hydrophobic and hydrophilic parts of the surfactant and water molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SDS and C 12 E 6 are widely used surfactant systems and have been studied extensively before. The interfacial structure of aqueous solutions of C 12 E 6 has recently been studied using HDVSFG, Kelvin-probe measurements, and molecular dynamics (MD) simulations 29 . In this study, it was found that C 12 E 6 at CMC (70 µm) generates a strong electric eld of 1 V/nm arising from the orientational structure of both the hydrophobic and hydrophilic parts of the surfactant and water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent change in the amplitudes of the C–H vibrations with SDS concentration is due to the rise of the low-frequency wing of the response of the water O–H vibrations with increasing SDS concentration. The positive water response of C 12 E 6 just by itself is explained in detail elsewhere . To briefly mention, the positive water signal between 3000 and 3400 cm –1 for solutions of C 12 E 6 results from the strong hydrogen bonding of water molecules to the ether groups of the headgroup of C 12 E 6 .…”
mentioning
confidence: 96%
“…The narrowing of the broad unstructured region into two sharp narrow features in region I indicates that the surface structure of Ch + becomes more uniform and ordered when the water content is increased. This type of structural change is commonly observed for surfactants at water surfaces when the concentration of polar species is increased. , With increasing water content, the Ch + ions acquire a more ordered and uniform alignment at the surface, thus removing the gauche conformation, as evident from the decrease of the signal at ∼2940 cm –1 . The spectral features in region II also change upon an increase of the water concentration, where the contribution to the vibrational spectrum from urea decreases (see Figure and Figure S2).…”
mentioning
confidence: 67%
“…Details of the experimental setup have been discussed in previous publications and are presented the Supporting Information. ,, Briefly, VSFG is performed by focusing two laser pulses and overlapping them on the sample spatially and temporally. One of the laser pulses, ω IR , is from a mid-infrared (mid-IR) source and is resonant with the vibrational frequencies of the molecules present at the surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The asymmetry of soft-matter interfaces with aqueous solutions generate electric fields that could be harnessed for chemical reactions [85][86][87] relevant in pre-biotic chemistry [88] as well as artificial photosynthesis. Both the statics and dynamics of water at the interface play a crucial role in controlling the magnitude and fluctuations of the electric field.…”
Section: Discussionmentioning
confidence: 99%